“Bring Us In Good Ale” and “The Maid and the Box”: English Social History Through Folk Song - C. Rouse, Andrew (FOCUS: Papers in English Literary and Cultural Studies, 2000)
Back in the early eighties, István Hegyi, lecturer at the music department of the newly-fledged Janus Pannonius University, Pécs, became acquainted with Norman Dannatt, then music adviser for the London Borough of Havering, when the latter, an elderly man whose musical background encompassed accompaniments for the silent movie to military bands and folklore, quite apart from his professional responsibilities in serious music and music education, was on the first of his many stays in Hungary. One evening, in the presence of the author, István asked his guest if he could provide him with an example of a “real folk song, you know, a pentatonic one.” To this request Norman jocularly replied, “Oh, all our songs are pentatonic, but they’re so boring like that that we put other notes in between to make them more interesting.”